The story Сhildhood as the beginning of Leo Tolstoy’s linguopoetic search - Romanov, Dmitry (Slavica, 2024)
The paper discusses the most prominent linguistic and poetic techniques in Leo Tolstoy’s story Childhood. Linguistic poetics is understood in a broad sense: with the inclusion of not only linguistic units themselves, but also compositional characteristics, stable plot moves, details of subject expressiveness, and effects on the reader. The evolution of the studied techniques in Tolstoy’s further work is traced.